DIFFERENT APPROACHES TO THE OBJECT ORIENTED CONSERVATION KNOWLEDGE: AN URBAN ARCHAEOLOGICAL RESEARCH - Doyduk, Senem; Can, Cengiz (YILDIZ TECHNICAL UNIV, 2012)
The urban accumulation in all areas of the city is conducted as a case even though the archaeological urban agglomeration is associated with accumulation of ground below. Urban spaces, these clutter environments are urban spaces which have the potential to be reached. The preservation of the urban accumulation of urban space is not only for conservation practices, but also about the preservation of the intellectual infrastructure of subjects is included in the study. The object of preservation discourse has an object-centered approach with the assumption that preservation problems are caused by this approach, the article constitutes a fundamental problem. Articles within the scope of protection granted to the tolerance of difference, the relationship between objects conservation, protection through the production of information, such as protection of the social issues are being investigated based on consensus.
Keywords: Urban archaeology; conservation; accumulation; urban open space; Engineering